El régimen jurídico disciplinario de los funcionarios públicos en el Ecuador - Marcalla Chiliquinga, Jenny Elizabeth (2011)
Discipline is a requirement for harmony and the proper functioning of any minimally organized group1 Therefore, when that requirement is not spontaneously met by those who are forced, the need for a power that guarantees the observance of established behaviors is naturally felt2 In any organization, public or private, the state ordinance or the particular ordinances grant to all of them a power of discipline, being the same essential to maintain order and ultimately guarantee the proposed purposes. Question that is of greater importance when we refer to the State Administration as an organization in which the public function is exercised and developed by the personal means in charge of it, taking into account its nature and functions, revealing that the orderly operation of it constitutes the legal asset protected by the discipline. In this sense, together with the obligation to continuously and diligently perform the function of the assigned work.